2003
DOI: 10.1679/aohc.66.337
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gastrin-releasing peptide (GRP) in the bovine uterus during the estrous cycle

Abstract: Gastrin-releasing peptide (GRP) has been proposed as a novel regulatory peptide in the reproductive tract. We previously demonstrated that GRP immunoreactivities are found predominantly in the uterine gland epithelial cells of nonpregnant and pregnant cows. The present study focused on the distribution of GRP immunoreactivity and the expression of GRP mRNA in the bovine endometrium during the estrous cycle. Tissues were collected from 21 uterine horns and bodies during the estrous cycle. RT-PCR showed the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…higher in UF) have previously been reported in the bovine uterus. This includes three which have been localised to GE [S100G, gastrin‐releasing peptide (GRP) and MIF] [], three which have been identified in uterine tissue (DBI, CTSD and PRDX6) [], and seven which have recently been detected in UF/fluid (RBP4, TPI, AKR1B1, HSPA8, EZR, TXN and PRDX1; where HSP stands for heat shock protein) [].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…higher in UF) have previously been reported in the bovine uterus. This includes three which have been localised to GE [S100G, gastrin‐releasing peptide (GRP) and MIF] [], three which have been identified in uterine tissue (DBI, CTSD and PRDX6) [], and seven which have recently been detected in UF/fluid (RBP4, TPI, AKR1B1, HSPA8, EZR, TXN and PRDX1; where HSP stands for heat shock protein) [].…”
Section: Resultsmentioning
confidence: 99%
“…GRP (6.1‐fold higher in UF compared to plasma) has been reported to modulate ion transport across human endometrial cells in vitro and may therefore influence the intra‐uterine environment []. The presence of GRP in the bovine uterus has been reported where it is localised to the gland cells of the bovine endometrium []. Uterine GRP may also play a role in implantation as it has been reported to affect cell adhesion, morphogenesis, migration and angiogenesis [].…”
Section: Discussionmentioning
confidence: 99%
“…(2003) revealed in the cow that RT‐PCR showed GRP mRNA fragments in the tissue during all stages of the cycle. Positive staining of GRP immunoreactivity in the uterine gland epithelial cells was also detected in both the uterine horn and body during all stages of the cycle in the cow (Budipitojo et al., 2003). It is also important to show the differences of GRP immunohistochemistry in their different estrous stages in the mouse deer.…”
Section: Discussionmentioning
confidence: 96%
“…It is necessary to evaluate other Ruminantia such as Moschidae, Cervidae, Giraffidae, Antilocapridae, which have polycotyledonary synepitheliochorial placentas; the suborders such as Suiformes and Tylpoda; and other orders such as Pholidota, which has a diffuse and epitheliochorial placenta, to compare and show the immunoreactivity of GRP in their uteroplacenta. Budipitojo et al. (2003) revealed in the cow that RT‐PCR showed GRP mRNA fragments in the tissue during all stages of the cycle.…”
Section: Discussionmentioning
confidence: 98%
“…It was found primarily in uterine gland epithelium at 20 and 140 days of gestation. Furthermore, GRP immunoreactivity has been described in the bovine uterus and cervix (Budipitojo et al., 2001, 2003, 2004a,b) as well as the placenta (Budipitojo et al., 2001). These investigators have suggested that GRP might play an important role in the autocrine and/or paracrine regulation of the intrauterine environment of both non‐pregnant and pregnant animals (Budipitojo et al., 2001, 2004a).…”
Section: Introductionmentioning
confidence: 99%